Internacionalização de PMEs por meio dos consórcios de exportação: uma análise dos modelos italiano e brasileiro - Carpes, Aletéia de Moura (2016)
The challenges for a small and medium sized company to build solid bases and obtain success in their activities are fierce. However, as companies need to respond to markets whose rhythm is continuously accelerating, and the internationalization emerge as a strategic alternative to survival and higher profits acquisition. However, as the internationalization is a complex activity, the formation of export consortia would minimize the challenges inherent, providing the companies to join their potential and share the risks of the activities. The consortia exports were originated in Italy and the Italian model is considered a reference in SME internationalization strategy. From that, this research sought to examine and compare the Brazilian consortia with the Italian, investigating how the consortiums in both countries are configured. Starting from the central concept of this study, which underpin that export consortia are made based on multi-level composition, the information obtained was analyzed from government agencies (Level 1), consortium management (Level 2) and firms Member (Level 3). Levels 1 and 2 were analyzed from a qualitative study, where FEDEREXPORT and APEX BRASIL representatives were interviewed, which are the Italian and Brazilian government agencies, in addition to 4 managers of consortia from both countries. In this first stage, the data were analyzed using content analysis techniques. The research was also based by a second phase of quantitative character and survey outlining, where the focus of the analysis was concentrated on Level 3, characterized by the member firms that integrate the consortia in both countries. Data feeds from 183 Italian companies and 200 Brazilian, univariate analyzes were performed to compare the different templates. By observing the results, it is worth highlighting that although the Brazilian consortia were originated based on the Italian model, there are considerable differences between the two, regarding, for example, the structure, legislation, consolidation, management approach and typology. In addition, it is worth pointing out that the Italian economic context has reflective negatively in the consortia, causing a considerable number of dissolutions and closures, endangering the reputation of a Italy consortium to succeed. In contravention, Brazilian consortia turn up to be in a favorable time for growth, showing the trend of expansion of BRICS in the international environment.